The art of hedging: Qatar, Saudi Arabia, and the UAE manoeuvres amid US–China great power competition - Ali Bakir (17917703) (2025)
The emergence of great power competition (GPC), primarily between the United States (US) and China, has compelled some Arab Gulf countries to recalibrate their foreign policies and adopt hedging behaviour. The growing economic and strategic ties between the Gulf Cooperation Council (GCC) states and China, alongside their traditional security alignment with the US, underscore the complexities of their hedging behaviour. Our paper explores the drivers behind the hedging behaviour of the GCC states (particularly Qatar, Saudi Arabia and the UAE), the variations in their approaches, and the future conditions that may alter the nature of hedging or the decision to engage in it. To address these issues, we adopt a qualitative approach, drawing on communications with several officials and experts from the Gulf, the US and China, as well as official statements, and empirical evidence across economic, political and defence realms. This methodology facilitates systematic observation and comparative analysis among the GCC members. Other Information Published in: Third World Quarterly License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01436597.2025.2509574